2010
DOI: 10.4103/0019-5545.69233
|View full text |Cite
|
Sign up to set email alerts
|

An overview of Indian research in obsessive compulsive disorder

Abstract: Obsessive-compulsive disorder (OCD) was considered a relatively rare disorder until about two decades ago. Since then, considerable advance has been made in understanding the various aspects of OCD that include epidemiology, clinical features, comorbidity, biology and treatment. In the last one decade, there has also been interest in a group of related disorders called obsessive-compulsive spectrum disorders. There is substantial research from India on various aspects of OCD, particularly from the National Ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 91 publications
1
19
0
Order By: Relevance
“…In addition, attention bias toward emotionally salient stimuli like “threat-related information” has been demonstrated in patients with OCD. [6225859] These findings are in support of the “threat-relatedness hypothesis” which proposes contents related to threat and associated cognitive processes to be the central characteristic of OCD. [60] Also, it has been suggested that treatment modifies meaning of these thoughts to that experienced by most other non-obsessional people.…”
Section: Neurocognitive Models Of Psychiatric Disorderssupporting
confidence: 65%
“…In addition, attention bias toward emotionally salient stimuli like “threat-related information” has been demonstrated in patients with OCD. [6225859] These findings are in support of the “threat-relatedness hypothesis” which proposes contents related to threat and associated cognitive processes to be the central characteristic of OCD. [60] Also, it has been suggested that treatment modifies meaning of these thoughts to that experienced by most other non-obsessional people.…”
Section: Neurocognitive Models Of Psychiatric Disorderssupporting
confidence: 65%
“…For instance, countries with stronger economies, such as Brazil, Russia, India, China, and South Africa (collectively known as the BRICS) were able to establish an early intervention program for psychosis and to perform relevant research in OCRDs (e.g. Reddy et al, 2010).…”
Section: Early Intervention In Low and Middle Income Countriesmentioning
confidence: 99%
“…Obsessive compulsive disorder (OCD) is the fourth most common mental disorder 9. In Indian setting, a study found that the lifetime prevalence of OCD was 0.6% 10. In Uttar Pradesh, which is the most populous state of India, the prevalence of OCD was 0.51% 11…”
Section: Introductionmentioning
confidence: 99%